Silaturrahim Perspektif Filsafat Islam (Ontologi, Epistemologi, Aksiologi) - M. Dzikrul Hakim Al Ghozali (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2016)
Gathering(silaturrahim) in a language derived from two words namely silah (relationship) and Rahim (Rahim women) that have meaning nasab Relations, as the verse above says al-Arham (womb) is defined as the gathering(silaturrahim). But in essence the relationship is not just a relationship nasab, but further than that relationships among Muslims is part of silaturrahmi, so God mengibarat the Muslims like one body. As the word of God. "Indeed the believers are brothers, therefore make peace between your brothers and fear Allah, that ye may obtain mercy." (Al-Hujurat [49]: 10). Fraternal relationship is what makes the fellow Muslims have an obligation to help each other, mutual respect, to visit when sick, drove up to the grave when he died, pray for one another, each denounced the ban, menghasud and others.Keywords: Philosophy and Gathering(silaturrahim).